Students’ Perception of Open Educational Resources for English Reading Material: English - Rifari Baron; Masrin (Prodi Tadris Bahasa Inggris, 2024)
The purpose of this study is to obtain students' perceptions of open educational resources as teaching materials for English reading learning. This study uses a descriptive qualitative method. The data collection process used observation, interviews, and documents. The selected participants were determined by the requirement that they had taken an English Reading course. The number of participants was 100 students. Data analysis used the stages of data reduction, data presentation, and conclusion. The findings concluded that six types of OER can be used as teaching materials in English reading classes, namely printed textbooks, online teaching materials, journals, technology applications, learning websites, and e-books. The use of technology applications is the most popular choice at 29% and technology applications provide practicality for students because they can access learning resources anytime and anywhere. The results of the study also showed a positive impact on improving students' reading habits and how they explore knowledge using OER.